The Analysis of University Student’s Critical Thinking in Writing Argumentative Essays in the English Department of UNESA - Arinta Cahyadewi; Yuri Lolita (Publikasi Indonesia, 2021)
Background: An argumentative essay is a reflection of students' critical thinking. Writing an argumentative essay means practicing critical thinking.Objective: To describe how critical thinking is reflected in argumentative writing and to find out how students respond in applying critical thinking in an argumentative essay.Methods: This research is descriptive qualitative as a research design. To obtain the data, the instrument used by the researcher was an assessment rubric and a questionnaire.Results: This shows that students' critical thinking skills in argumentative writing are pretty good, and they can solve the problems they face by relying on their critical thinking. In conclusion, most of the students apply their critical thinking in writing argumentatively well.Conclusion: This study found that the argumentative essays written by the research subjects were reasonable based on the scoring rubric used in this study. Students are also able to use their critical thinking in developing an argumentative essay